2010
DOI: 10.1002/ijc.25661
|View full text |Cite
|
Sign up to set email alerts
|

MT119, a new planar‐structured compound, targets the colchicine site of tubulin arresting mitosis and inhibiting tumor cell proliferation

Abstract: Microtubule-targeted drugs are now indispensable for the therapy of various cancer types worldwide. In this article, we report MT119 [6-[2-(4-methoxyphenyl) -ethyl]-9-[(pyridine-3-ylmethyl)amino]pyrido[2 0 ,1 0 :2,3]imida-zo [4,5-c]isoquinolin-5(6H)-one] as a new microtubule-targeted agent. MT119 inhibited tubulin polymerization significantly both in tumor cells and in cell-free systems, which was followed by the disruption of mitotic spindle assembly. Surface plasmon resonance-based analyses showed that MT11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…We reported that specific compounds can directly kill MDR tumor cells without affecting the function of P-gp, such as the natural products salvicine (3,4), pseudolaric acid B (5, 6), methyl spongoate (7), tanshinone I (2,8), and synthetic small molecules YCH337 (9) and MT series (10)(11)(12). Among them, the MDRovercoming activities of natural products were associated with the regulation of certain transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…We reported that specific compounds can directly kill MDR tumor cells without affecting the function of P-gp, such as the natural products salvicine (3,4), pseudolaric acid B (5, 6), methyl spongoate (7), tanshinone I (2,8), and synthetic small molecules YCH337 (9) and MT series (10)(11)(12). Among them, the MDRovercoming activities of natural products were associated with the regulation of certain transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported MT7 and MT119 derived from a combinatorial library of 6H-Pyrido[2 0 ,1 0 :2,3]imidazo [4,5-c]isoquinolin-5(6H)-ones as colchicine site-targeted tubulin inhibitors (2-4). They are new chemical entities with a distinct mode of tubulin polymerization inhibition from colchicines, but disappointingly, both do not show in vivo anticancer activity (3,4). MT189 is a newest analog of this series, obtained by taking a deconstruction approach to break the tetracyclic ring of MT119.…”
Section: Discussionmentioning
confidence: 99%
“…Both cause microtubulin depolymerization, persistent M phase arrest, and apoptosis. MT119 was confirmed to bind to the colchicine site on tubulin (3)(4)(5). Although both produce potent in vitro antiproliferative effects and overcome tumor multidrug resistance (MDR), they did not show obvious in vivo anticancer activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are composed of α and β tubulin heterodimers that are involved in numerous cellular functions including motility, division and intracellular transport. [1][2][3][4][5][6] A number of small molecules bind tubulin interfering with microtubule polymerization and depolymerization, thereby inducing cell cycle arrest leading to apoptosis. It is known that the antitumor efficacy of many chemotherapeutic agents is correlated to their ability to promote apoptosis in cancer cells.…”
mentioning
confidence: 99%